Landscape Connectivity and Wildlife Access to Water Across an International Border: Barriers and Opportunities for Facilitating Transboundary Movement - Bogdan Chivoiu; Erin L. Koen; Michael J. Osland; Christopher A. Gabler; Jerald T. Garrett; Ernesto Reyes; Stephanie A. Bilodeau; Mitch A. Sternberg; Miguel L. Villarreal; Eric K. Waller; Samuel N. Chambers; Jude A. Benavides; et al. (Global Change Biology, 2026)
Rapid global acceleration in the construction of physical barriers along international borders has greatly influenced biodiversity and animal movement. Physical barriers can fragment landscapes, hinder access to essential resources, impact long‐distance migrations, and inhibit dispersal and gene flow. The effects of physical barriers on animal movement and landscape connectivity can be exacerbated in dryland environments where access to water is a limiting factor. In recent decades, the construction of border barrier infrastructure has accelerated along the international boundary between the United States and Mexico. Here, we used a landscape connectivity model to investigate the effects of barriers on wildlife access to the river in the Lower Rio Grande Valley. We used a modified omnidirectional connectivity model to compare access to the river for three large, terrestrial mammal species across three border barrier scenarios: (1) a landscape without border barriers; (2) a landscape with the existing barrier system; and (3) a potential future landscape with a continuous barrier system. The existing barrier system includes many discrete sections of barrier within tracts of the Lower Rio Grande Valley National Wildlife Refuge or on lands associated with the region's flood control system. Our results indicate that the existing border barriers can impede connectivity and wildlife access to the river in some areas, while some existing gaps between border barrier sections can serve as conduits for wildlife movement and river access. Our future scenario results show how a potential continuous border barrier system could further impede wildlife access to the river. We discuss management and landscape conservation options for enhancing wildlife access to water and riverine habitats. Collectively, our results illustrate the potential effects of border barriers on wildlife movement and access to water, providing information that can be used to better anticipate and lessen the ecological impacts of transboundary barriers.